Managing Cancer Care: a psycho‐educational intervention to improve knowledge of care options and breast cancer self‐management. Issue 2 (4th November 2015) - Schulman‐Green, Dena; Jeon, Sangchoon
Abstract: Objective: We tested the feasibility and acceptability of a psycho‐educational self‐management intervention, Managing Cancer Care : A Personal Guide ( MCC ), to improve knowledge of care options (curative, palliative, and hospice care) among a range of breast cancer self‐management skills. Methods: We conducted a one‐group, pre‐post‐test study among women with non‐metastatic breast cancer ( n = 105). We gave participants the printed, self‐guided, seven‐module intervention following enrollment. At baseline and 2 months, we measured knowledge of care options, desired and actual role in self‐management, medical communication skills, experience and management of transitions, anxiety, depression, uncertainty, and self‐efficacy. We conducted interviews to obtain module ratings and qualitative data on strengths and limitations of MCC. Results: Knowledge of care options (δ = 0.40 (1.11), p = 0.0005) and desired role in self‐management (δ = −0.28 (1.08), p = 0.0177) significantly improved. Less skilled medical communicators significantly improved their communication (δ = 3.47, standard deviation = 6.58, p = 0.0449). Multivariate modeling showed that changes in our primary outcomes of medical communication and management of transitions seemed to drive positive changes in our secondary outcomes of anxiety, depression, uncertainty, and self‐efficacy. Participants highly rated MCC and reported the importance of understanding care options despite non‐metastatic disease. Conclusions: MCC is a feasible and acceptable means of improving knowledge of care options and other aspects of breast cancer self‐management. The combination of modules offered in MCC appears to have beneficial interactive effects. We are currently testing MCC more rigorously in a randomized controlled trial to explore mediating and moderating relationships. Copyright © 2015 John Wiley & Sons, Ltd.